Medial-lateral hip positions predicted kinetic asymmetries during double-leg squats in collegiate athletes following anterior cruciate ligament reconstruction - Song, Y.; Li, L.; Albrandt, E. E.; Jensen, M. A.; Dai, B. (Journal of Biomechanics, 2021)
ACL re-injury rates are high in collegiate athletes, and double-leg squats have been used as a functional weight-bearing exercise to strengthen the lower extremities and assess bilateral kinetic asymmetries. The primary purpose was to quantify the correlations between medial-lateral shoulder/hip positions and lateral bending angles and bilateral asymmetries in vertical ground reaction forces (VGRF) and knee extension moments during double-leg squats in collegiate athletes at two assessments following anterior cruciate ligament reconstruction (ACLR). Seventeen National Collegiate Athletic Association Division I athletes performed double-leg squats between 0 and 6 months and/or between 6 and 12 months following their ACLR while kinematic and kinetic data were collected. Medial-lateral shoulder positions strongly and significantly correlated with VGRF asymmetries at both assessments (p = 0.007, r = 0.68). Medial-lateral hip positions strongly and significantly correlated with VGRF asymmetries and knee moment asymmetries at both assessments (p = 0.018, r = 0.62). Additionally, participants demonstrated decreased VGRF asymmetries and knee moment asymmetries, more neutral shoulder and hip positions, and increased knee moments for the injured leg at the second assessment compared to the first assessment with large effect sizes (p = 0.008, Cohen`s d = 1.06). In conclusion, medial-lateral hip positions correlated and predicted VGRF and knee moment asymmetries during double-leg squats in collegiate athletes at two assessments (0-6 and 6-12 months) following ACLR. The bilateral asymmetries support the need for an individual approach for kinetic asymmetry assessments. A commercially available camera can be utilized as a low-cost and convenient tool to monitor and potentially train bilateral kinetic symmetries during double-leg squats in patients following ACLR.